Molecular characterization of alpha globin and beta globin genes in patients with hemoglobinopathies in Central Vietnam - Le, Phan Tuong Quynh; Ha, Thi Minh Thi; Tran, Thi Nhu Nga; Le, Phan Minh Triet; Ton, That Minh Tri; Dong, Si Sang; Phan, Thi Thuy Hoa; Le, Tuan Linh (Tạp chí Y Dược Huế, 2022)
Background: Hemoglobinopathy is the most common monogenic disease worldwide. The aims of the current study were: (1) to investigate some hematological characteristics of patients with hemoglobinopathies; and (2) to detect the mutation of α-globin and β-globin genes, as well as the association between genotype and degree of anemia. Materials and method: 251 patients with hemoglobinopathies were examined for the α-globin or β-globin gene mutations. Results: 51% were the carriers, and 49% were thalassemia intermedia or thalassemia major. Hematological characteristics were suitable for α-thalassemia or β-thalassemia. Eleven β-globin gene mutations were observed . The β0/βA, βE/βA, βE/βE, βE/β+, β+/β+ genotypes were only found in β-thalassemia intermedia individuals; the β0/β0 genotype was limited to β-thalassemia major patients; the β+/β0 and βE/β0 genotypes were seen in both types. Four α-globin gene mutations were observed. All α-thalassemia patients were intermedia, the most common genotype was –SEA/-α3.7. Conclusion: There were differences in anemia degree between β-globin genotypes.